Persepsi Guru Sekolah Dasar terhadap Media Pembelajaran STEM di Kota dan Kabupaten Tasikmalaya - Maulidah, Siti; Hamdu, Ghullam; Putri, Agnestasia Ramadhani (Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
This study aims to describe elementary school teachers’ perceptions of the use of STEM-based instructional media as an effort to strengthen 21st-century skills. The research employed a descriptive qualitative approach with the subjects being elementary school teachers in the regions of Tasikmalaya City and Regency. The population included all elementary school teachers in both areas, with a purposive sample of 50 participants. The research instrument was a Likert-scale questionnaire developed based on three indicators of STEM literacy: (1) awareness of the role of STEM in modern society, (2) familiarity with basic STEM concepts, and (3) foundational fluency in STEM application. Data were collected using an online questionnaire via google forms, while the data analysis involved calculating the average score for each indicator. The results showed that for the first indicator, teachers in Tasikmalaya City had higher awareness (average score of 4.05) compared to those in the Regency (3.93). However, in the second and third indicators, teachers from the Regency scored higher, at 3.39 and 3.67 respectively, compared to city teachers who scored 3.30 and 3.59. These findings suggest that although urban teachers have stronger conceptual awareness, rural teachers demonstrate greater mastery in understanding and applying STEM practically in classroom learning. This difference is suspected to be influenced by contextual experience and more frequent implementation of hands-on learning approaches in the Regency.